2010
DOI: 10.1016/j.ygcen.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of C-type allatostatin (C-AST)-like immunoreactivity in the central nervous system of the copepod Calanus finmarchicus

Abstract: The C-type Allatostatins (C-ASTs) are a family of highly pleiotropic arthropod neuropeptides. In crustaceans, transcriptomic/mass spectral studies have identified C-ASTs in the nervous systems of many species; the cellular distributions of these peptides remain unknown. Here, the distribution of C-AST was mapped in the nervous system of the copepod Calanus finmarchicus, the major contributor to the North Atlantic's zooplanktonic biomass; C-AST-immunopositive neurons were identified in the protocerebrum, in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Figure 4 shows the localization of three major neuropeptide families in C. sapidus PO: AST-B, RYamide and FLPs, all of which are shown to be involved in feeding behavior of crustaceans based on previous reports [2, 5, 19, 42]. Several isoforms of the AST-B family display colocalization patterns in the PO, including VPNDWAHFRGSWamide ( m/z 1470.70), AGWSSMRGAWamide ( m/z 1107.52), and a novel isoform, SGDWSSLRGAWamide ( m/z 1220.58), with a high concentration in the posterior bar region, dorsal trunk and anterior bar region.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the localization of three major neuropeptide families in C. sapidus PO: AST-B, RYamide and FLPs, all of which are shown to be involved in feeding behavior of crustaceans based on previous reports [2, 5, 19, 42]. Several isoforms of the AST-B family display colocalization patterns in the PO, including VPNDWAHFRGSWamide ( m/z 1470.70), AGWSSMRGAWamide ( m/z 1107.52), and a novel isoform, SGDWSSLRGAWamide ( m/z 1220.58), with a high concentration in the posterior bar region, dorsal trunk and anterior bar region.…”
Section: Resultsmentioning
confidence: 99%
“…For over 40 years, immunohistochemisty has been the primary method used for mapping neurochemical distributions in crustaceans (e.g., Jaros and Keller 1979;Van Herp and Van Buggenum 1979;Hartline and Christie 2010;Sharp et al 2010;Wilson and Christie 2010). Via this method, numerous molecules, including peptides, amines, small molecule transmitters and diffusible gases (e.g., Christie et al 1995aChristie et al , 2003Christie et al , 2004aPulver and Marder 2002;Fu et al 2005b), have been identified and/or mapped in crustacean neuroendocrine organs.…”
Section: A Recent Advance In Mapping the Distributions Of Crustacean mentioning
confidence: 99%
“…They are also present in the nervous system of a non-malacostracan crustacean, the copepod Calanus finmarchicus [42]. In the current study we set out to analyze the role of A-ASTs in the crustacean brain in more detail by analyzing their distribution in the terrestrial hermit crab Coenobita clypeatus (Anomura, Coenobitidae) focussing on its central olfactory pathway.…”
Section: Introductionmentioning
confidence: 99%